Case report and surgical video presentation: Combined laparoscopic and cystoscopic partial bladder cystectomy for excision of deeply infiltrating endometriosis. (November 2018) - Pontré, Jennifer C.; Yin, Jessica M.A.; Brown, Bernadette; Karthigasu, Krishnan; McElhinney, Bernadette
Abstract: Introduction: Whilst endometriosis is a relatively common condition, deeply infiltrating endometriosis (DIE) of the bladder is less so, and when medical treatment fails, surgical management is an effective option. We present a case report and surgical video of a patient undergoing combined laparoscopic and cystoscopic excision of deeply infiltrating endometriosis of the bladder. Design: Case report (Canadian Task Force Classification III) and step-by-step explanation of the surgery using video. Exemption was granted from the local institutional review board. Presentation of case: We present a case report and surgical video of a 36-year-old nulliparous patient presenting with a 12-month history of sudden onset cyclical dysuria and haematuria. Imaging demonstrated a deeply infiltrating endometriotic nodule involving the bladder. The patient underwent a combined laparoscopic and cystoscopic excision of deeply infiltrating endometriosis of the bladder. The procedure was uneventful and the patient progressed to a full recovery. Discussion: DIE is a highly invasive form of endometriosis which is defined arbitrarily as endometriosis infiltrating beneath the peritoneum by 5mm or greater. When medical therapy is declined or fails, surgical excision by partial cystectomy would appear to be the most effective management option. A combination of cystoscopy and laparoscopy has been shown to be a safe and feasible procedure, with a low rate of complications. It represents the ideal way by which to identify the resection limits for complete excision of the lesion, and allows for optimal repair of the bladder defect. Conclusion: Combined laparoscopic and cystoscopic partial cystectomy for excision of deeply infiltrating bladder endometriosis is a safe and feasible procedure in our institution. Highlights: A case of surgical management of deeply infiltrating endometriosis of the bladder is reported. Combined cystoscopic and laparoscopic excision can be performed for the treatment of this form of endometriosis. This approach is safe, feasible and has a low rate of complications in the current literature.